2022
DOI: 10.1002/adfm.202207282
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Efficiency of Organic Solid‐State Lasers by Solvato‐Tailored Assemblies

Abstract: The photophysical properties of pure organic materials in solid-state are widely related to the crystal's arrangements. Herein, 4,6-bis((E)-4-(dibenzothiophene) styryl)-5(ethoxycarbonyl)-2,2-difluoro-2H-1,3,2-dioxaborinin-1-ium-2-uide (BBSF) is employed as a mode molecule to explore the relationship between molecular arrangement and performance. Three elegant crystals (solventfree-J-aggregation of EA-crystal, solvent-J-aggregations of CB-crystal, and FB-crystal) are obtained by solvato-tailored strategy. Detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Organic solid-state emissive materials have found extensive applications, such as light-emitting diodes (LEDs), , solid-state lasers, , optical waveguides, , and luminescent sensors. , Among these materials, those with tunable emissions have garnered increasing attention due to their potential in multicolor displays, multiplexed imaging, information encryption, and anticounterfeiting technologies . However, the rational design of such materials based on a single fluorophore remains a formidable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Organic solid-state emissive materials have found extensive applications, such as light-emitting diodes (LEDs), , solid-state lasers, , optical waveguides, , and luminescent sensors. , Among these materials, those with tunable emissions have garnered increasing attention due to their potential in multicolor displays, multiplexed imaging, information encryption, and anticounterfeiting technologies . However, the rational design of such materials based on a single fluorophore remains a formidable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Organic crystals have garnered significant attention owing to their inherent advantages of anisotropic properties and well-ordered packing structures. These distinctive characteristics render them promising candidates for optoelectronic applications, such as organic light-emitting diodes, organic solid-state lasers, and optoelectronic resonators. Nevertheless, the superiority of organic crystals over metal or polymer materials remains a topic of debate among researchers. This divergence in opinion is largely attributed to a critical drawback of crystals, namely, their brittleness.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that BBSF molecules possess the merits of excellent SE performance, large Stokes’ shift, and high photostability. [ 28 ] CBP is the most widely used host materials for OLEDs with high crystallization. [ 29 ] We first prepared BBSF@CBP microcrystals with a diameter ≈of 5–8 µm by reprecipitation method.…”
Section: Introductionmentioning
confidence: 99%